"Having friends is like having marshmallows": Perspectives of transition‐aged youths with intellectual and developmental disabilities on friendship. Issue 6 (27th June 2018) - Hurd, Claire; Evans, Cara; Renwick, Rebecca
Abstract: Background: The literature emphasizes that friendships are essential to youths' successful transition to and adjustment in adulthood. Few studies have explored the friendships of transition‐aged youths with intellectual and developmental disabilities (IDD), and even fewer include youths' own perspectives. This qualitative study explored the perspectives of transition‐aged youths with IDD regarding their own experiences of friendship. Method: A subset of video‐recorded data of 21 interviews with seven participants (20–24 years) was extracted from a larger study for secondary analysis. Data were analysed using thematic analysis, informed by constructivist grounded theory methods. Results: Three themes were revealed: meanings of friends and friendship, deepening self‐knowledge and negotiating in(ter)dependence. Conclusions: The findings expand existing knowledge about friendships of transition‐aged youths with IDD. Findings can potentially inform development of new services or enhancement of existing services aimed at facilitating transition to adulthood for youths with IDD and point to key areas for future research.